(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The COVID-19 pandemic has impacted changes in people’s consumption patterns, namely from fundamental markets to online markets, so there needs to be an adaptation from MSME actors. MSMEs are one of the economic sectors that support the economy, especially in developing countries such as Indonesia. MSMEs in Kapanewon Turi, Sleman Regency is one the MSMEs with high potential to develop. However, institutional strengthening is needed for the MSME community in this region because there is no coordination and organization in an MSME community in Kapanewon. In addition, the Packaging of some MSMEs is not up to standard, branding is not yet strong, and the information technology capabilities of MSME actors are still low. Based on these problems, a solution for each problem is needed. Community formation and institutional strengthening of MSMEs were formed and continued with legal registration to become PT MSMEs by presenting resource persons from the Kapanewon Turi office. MSME actors are assisted in registering a NIB (Enterprise Identification Number) to achieve the legality of PT MSMEs. Then, increasing the knowledge and skills of MSME actors in terms of Packaging, branding, and digital marketing is carried out through counseling, training, and mentoring activities. The result of this service is that most MSMEs participants who already have a NIB and take part in counseling, training, and mentoring experience increased their knowledge and skills in Packaging, branding, and digital marketing.